CRITICAL THINKING IN PATHOPHYSIOLOGY - Swinney, Heather (Acta Scientiae et Intellectus, 2024)
As failure to rescue and patient safety have been brought to the forefront of health care concerns, so has the awareness that a considerable number of graduate nurses are unable to critically think to make decisions about care and meet objectives (del Bueno, 2005 as cited by Lewis, 2017). There is an abundant amount of information regarding fostering critical thinking in nursing. However, it is evident that developing critical thinking is not enough. An understanding of pathophysiology is essential to success in nursing education. Therefore, it is suggested that critical thinking be encouraged in pathophysiology, generally a prerequisite course, when the foundation for nursing education is being established instead of to waiting to promote critical thinking in nursing curriculum. Additionally, several learning strategies suggestive to promote critical thinking are reviewed.